Inflammatory Arthritis following Hepatitis B Vaccination in an Infant - Rahimi, Sana S.; Ostrov, Barbara E.; Lopez-Pena, Maricarmen (Case Reports in Rheumatology, 2021)
Inflammatory arthritis in children may be idiopathic in nature or may be due to or follow infections. Rare reports identify inflammatory arthritis temporally related to vaccination in children. Herein, we describe the first reported case of an infant who developed inflammatory arthritis following hepatitis B vaccination. A 10-day-old female presented for evaluation of decreased movement of the right lower extremity and right knee swelling. Of note, the patient received a hepatitis B vaccine in her right thigh at birth. A workup found the patient to have a negative ANA but the presence of HLA B27. Findings resolved using ibuprofen. A literature review identified reports of what has been termed “reactive arthritis” in adult patients following the hepatitis B vaccine, frequently in association with HLA B27. No prior pediatric cases have been published. Healthcare providers must be aware of the rare development of postvaccination inflammatory arthritis.